2000
DOI: 10.1093/ajcn/71.2.544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium supplementation on bone mineral accretion in Gambian children accustomed to a low-calcium diet

Abstract: Increased calcium intake resulted in increased bone mineral status, possibly in association with a decreased bone remodeling space. Further studies are needed to determine whether an increased calcium intake has long-term benefits in Gambian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(130 citation statements)
references
References 22 publications
3
122
1
Order By: Relevance
“…Several intervention studies have shown a reduction in bone turnover after calcium supplementation in children. In a randomized, double-blinded trial, conducted on predominantly prepubertal children, significantly lower (P ¼ 0.001) s-OC concentrations were seen in a calcium supplemented group (1000 mg/day) compared with a placebo group (Dibba et al, 2000). Similarly, monozygotic-twins, supplemented with 1000 mg/day calcium for 3 years, had lower (Po0.05) s-OC concentrations compared to a placebo group (Johnston et al, 1992;Slemenda et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Several intervention studies have shown a reduction in bone turnover after calcium supplementation in children. In a randomized, double-blinded trial, conducted on predominantly prepubertal children, significantly lower (P ¼ 0.001) s-OC concentrations were seen in a calcium supplemented group (1000 mg/day) compared with a placebo group (Dibba et al, 2000). Similarly, monozygotic-twins, supplemented with 1000 mg/day calcium for 3 years, had lower (Po0.05) s-OC concentrations compared to a placebo group (Johnston et al, 1992;Slemenda et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…However, previous work in this community has shown that puberty is delayed as compared to British reference children. 10 It is therefore unlikely that children of this age will have reached puberty. All the Italian children in the study were known to be healthy.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary requirements for calcium (Ca) and phosphorus (P) are increased and almost 50% of total bone mineral is deposited at 9-18 y in females and 10-20 y in males (Matkovic, 1991). Several Ca supplementation studies have been conducted in children and adolescents, which have shown that Ca supplementation is associated with increases in bone mineral content, which may be attributable to a reduction in bone turnover rate mediated by reduced parathyroid hormone (PTH) secretion (Johnston et al, 1992;Lloyd et al, 1993;Cadogan et al, 1997;Slemenda et al, 1997;Dibba et al, 2000;Wastney et al, 2000;Ginty et al 2002a, b;Prentice et al, 2002;Stear et al, 2003). In adults, other nutrients have been postulated to have direct and/or indirect effects on Ca and bone metabolism and bone mineral status, including magnesium (Mg) (Sojka & Weaver, 1995;Tucker et al, 1999;New et al, 2000), vitamin D (Holick, 1996), and potassium (K) (Sojka & Weaver, 1995;Tucker et al, 1999;New et al, 2000).…”
Section: Introductionmentioning
confidence: 99%